High isolation and absorptive feature in single pole double throw (SPDT) discrete switch design using switchable matched ring resonator - Shairi, N.A. (American Scientific Publishers, 2015)
An application of switchable matched ring resonator in Single Pole Double Throw (SPDT) discrete switch for Time Division Duplex (TDD) switching of wireless communications is proposed in this paper. Discussions of the conceptual and operation of the ring resonator and SPDT discrete switch are reported. Theoretically, high isolation and absorptive feature in SPDT switch can be obtained by the use of the matched ring resonator that can be switched between bandstop and bandpass response. The proposed SPDT switch circuit is further simulated in an electronic design automation software for analysis and fabricated for validation. Frequency spectrum in 2.010â2.025 GHz band for TD-SCDMA is chosen to demonstrate this technique. A good agreement is shown between the simulated and measured results; hence, more than 15 dB return loss at absorptive port and more than 30 dB isolation at resonant frequency can be obtained by using switchable matched ring resonator in SPDT discrete switch design. Â© 2015 American Scientific Publishers. All rights reserved.